Eco-friendly management of late blight ( Phytophthora infestans,(Mont.) de Bary) of tomato in hill conditions of Meghalaya - Dkhar, Mariana; Dutta, Ram (Umiam : CPGS, CAU, 2009)
The present investigation was carried out lor two consecutive years (2007-08 & 2008-09), which included study of Phytophthora infestans incidence at various growth stages of tomato, screening of 12 tomato genotypes for resistance /tolerance and evaluation of three bio-control agcnts/ two botanicals and four fungicides for management of late bl ight of tomato. There were significant differences in respect of disease rating and yield in both the cropping seasons. Among genotypes. CO-3 was found moderately susceptible and Rocky as highly susceptible. Whereas. rest of the genotypes were susceptible having varying degree of susceptibility. under mid-hill conditions of Meghalaya. The yield Among botanicals evaluated. MA TW-2 (native organic formulation) was found effective in managing the disease being next to fungicide, Ridomil MZ 72. Among Bio-control agents, the highest disease management was received by Nisarga compared to control. In in-vitro evaluation of botanicals. bio-control agents and fungicides, the medium amended with MATW-2 reduced the maximum mycelial growth among botanicals, Nisarga among bio-control agents and Ridomil MZ 72 among fungicides, in terms of radial growth (cm). It was concluded from the stud) that genotype CO-3 was found promising for cultivation in mid-hill conditions of Meghalaya and botanical MATW-2 in reducing the disease as well as enhancing the yield, hence. may be recommended for the management of late blight of tomato.
Keywords: Tomato -- Fungus diseases; Phytopthora infestans; Plant Pathology